2006
DOI: 10.1038/sj.ejcn.1602443
|View full text |Cite
|
Sign up to set email alerts
|

PDA-assisted low glycemic index dietary intervention for type II diabetes: a pilot study

Abstract: Background: Epidemiological and dietary intervention studies suggest that a low-glycemic index (GI) diet is beneficial for blood glucose control; however, long-term clinical utility of the low GI diet has not been fully investigated. Objectives: To evaluate the feasibility and efficacy of a nutritionist-delivered low-GI dietary intervention, with the support of a personal digital assistant (PDA), for adult patients with poorly controlled type II diabetes. Method: The low-GI intervention consisted of six counse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Da Silva et al [29] found that hip circumference can be reduced after the consumption of 20 g of green banana flour/ day, which is rich in fibers, for 45 days in 25 overweight women. Ma et al [30] examined the efficacy of a nutritionist-delivered low-GI dietary intervention, with the support of a personal digital assistant (PDA), for 13 adult patients with poorly controlled type 2 diabetes. Among many other parameters, hip circumference was decreased significantly after 6 months of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Da Silva et al [29] found that hip circumference can be reduced after the consumption of 20 g of green banana flour/ day, which is rich in fibers, for 45 days in 25 overweight women. Ma et al [30] examined the efficacy of a nutritionist-delivered low-GI dietary intervention, with the support of a personal digital assistant (PDA), for 13 adult patients with poorly controlled type 2 diabetes. Among many other parameters, hip circumference was decreased significantly after 6 months of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of the glycemic index (GI) has provided the scientific community with a new way to examine the quality of carbohydrate (CHO), which has been useful in research on the etiology and prevention of diabetes, coronary heart disease, obesity, prostate cancer, and other chronic diseases [1][2][3][4][5][6]. Historically, CHOs have been classified into two major forms: complex and simple.…”
Section: Introductionmentioning
confidence: 99%
“…Users wanted the food-specific information to include suggestions for alternative foods, comparison based on nutritional content, ways of preparing the food, and energy content in relation to recommended energy intake from protein, fat, and carbohydrate. Relevant literature 20,21 describes the use of food information on handheld devices and the difficulties in finding food items a user wants-even though, or because, the database contains several thousand food items. Especially for people with T2DM, it seems to be more important to get approximate ideas of how much impact a food item has on the BG level than to record very precise amounts of carbohydrate.…”
Section: Nutrition Information For Type 2 Diabetesmentioning
confidence: 99%